Evaluating the frequency of operational research conducted during the 2014–2016 West Africa Ebola epidemic. (December 2018) - Hurtado, Christopher; Meyer, Diane; Snyder, Michael; Nuzzo, Jennifer B.
Highlights: Most publications about the 2014–2016 Ebola epidemic were not related to operational research. Operational research studies tend to be published after outbreaks are declared over. Additional operational research studies are needed to inform future responses. Abstract: Introduction: The West Africa Ebola epidemic of 2014–2016 was the largest Ebola outbreak on record, and thousands of individuals were involved in the response, including local and national governments, as well as numerous philanthropic and other non-governmental organizations. A number of after-action reports and other reviews of the global response to the epidemic routinely pointed out key challenges, including gaps in operational research. Methods: To determine the extent to which operational research studies were conducted during the 2014–2016 West Africa Ebola epidemic, a quantitative analysis of the literature published during and immediately after the epidemic was conducted. The goal was to identify the proportion of all Ebola-related publications released regarding the epidemic that addressed operational aspects of the response. It was also sought to describe, at a general level, the sorts of studies that were published during the epidemic, with the goal of increasing understanding of whether additional efforts are needed to encourage the conduct and dissemination of operational studies during future public health crises. Results: Among the 3681 publications on Ebola published between the World Health Organization announcement of the Ebola outbreak in March 2014 and the end of 2017, 109 (3%) were determined to be operational research publications. Among these, 64 (58%) were published after the World Health Organization initially declared the outbreak over on January 14, 2016, reflecting the time delay of sharing operational lessons with the broader preparedness and response community. Discussion: Improved sharing of firsthand, operational knowledge from practitioners who respond to outbreaks is critical for improving preparedness activities and informing the development of sound, effective policies that support ongoing and future preparedness efforts. Based on the results from this review, we propose several policy and programmatic innovations that could facilitate knowledge sharing during future outbreaks.